Ecology of egrets (Ardeidae) at the palm oil mill effluent ponds in Carey Island, Selangor, Peninsular Malaysia / Abdoul Baset Hassen Aboushiba - Aboushiba, Abdoul Baset Hassen (2013)
Egrets (Aves: Ardeidae) are gregarious and cosmopolitan wading birds, widely distributed throughout the world and associated with wetland habitat particularly with shallow water covered with short vegetation or without vegetation for foraging. A wetland habitats are facing overwhelming pressure due to anthropogenic activities such as urbanization and conversion into agricultural fields which causes habitat loss and degradation that ultimately affects the population of different egret species. Egrets employ different foraging behaviours to exploit the wide range of prey items for their survival and reproduction. Study on egrets’ relative abundance, foraging strategies, food diversity, and its relationships to the quality of water of various Palm Oil Mill Effluent (POME) ponds in Carey Island, Selangor, Peninsular Malaysia was conducted from January 2008 to December 2008. Egret’s abundance was recorded using binoculars and a digital video camera, availability of their food resources was sampled by scope net, and water quality parameters were measured using YSI hydro lab. A total of 14,077 sightings of egrets was recorded. These egrets belong to five species, i.e. Little Egret (Egretta garzetta), Great Egret (Casmerodius albus), Cattle Egret (Bubulcus cormorandus), Intermediate Egret (Mesophoyx intermedia) and Chinese Egret (Egretta eulophotes). The ANOVA and Tukey’s test showed that the relative abundance of Cattle, Intermediate and Chinese Egrets were significantly different from Little and Great Egrets (F4, 55 = 17.58, P < 0.05). Results also indicated that Little Egrets had the highest probing activity (52 probes/minute) while Great Egrets had the lowest probing activity (5 probes/minute). It was observed that egrets employed different foraging strategies in obtaining aquatic invertebrates. Only Little Egret employs foot shuffling technique and only Cattle Egret glean the prey hidden v under soft mud. A total of 119,126 invertebrate larvae (belong to twelve species) were sampled by scoop nets. Larvae were sampled from POME ponds No. 3 (51.40%) and No. 1 (48.60%) but none were recorded from ponds two and four. Mosquito (Aedes sp.) larva was abundantly recorded (40.71%) while water scavenger beetles (Hydrophilus sp.) were the rarest (2.52%). The highest invertebrate species diversity was recorded in POME pond No. 1 (Shannon’s N1 = 2.21) and POME pond No. 3 (N1 = 2.17) while the highest species evenness was recorded in June 2009 (Pielou’s E = 0.89 in pond No. 1 and E = 0.87 in pond No. 3). The highest relative abundance of egrets was recorded in January 2008 (14.00%) and the lowest was recorded in August 2008 (3.36%). It was also found that egrets were active (22.33%) during the morning (from 0900 to 1000 hours) and less active (5.72%) during mid-day (1300 to 1400 hours). Relative abundance of egrets in POME pond No. 2 and No. 4 was significantly different (F3, 16 = 5.70, P < 0.05). The highest egret’s species diversity (N1 = 3.82) and evenness (E = 0.83) were recorded in pond No. 1 but the highest egret’s species richness was recorded in pond number three (R1 = 0.46). For water parameters, the highest water temperature (35.360C), conductivity (5685 μs), and turbidity (89.6NTU) were recorded in pond No. 1 in January 2009 while the highest record for the dissolve oxygen (3.73mg/l), pH (8.97), and ammonium concentration (28.05mg/l) were recorded in February 2009. Pearson’s Correlation Coefficient (PCC) test revealed that egret species have a weak relationship with water quality parameters, invertebrate abundance and a weak positive relationship between egret foraging activities. Based on the findings of this research, it is concluded that POME ponds one and three are highly important habitats and foraging sites for egrets. Food abundance and distribution are the most important factor in determining the quality of the feeding areas and habitat selection by egrets.